1997
DOI: 10.1103/physrevb.56.1568
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-dynamics study of diamond/silicon (001) interfaces with and without graphitic interface layers

Abstract: A theoretical study of diamond/silicon ͑001͒ interface structures with and without graphitic interlayers using a density-functional based tight-binding molecular-dynamics method is presented. The study is motivated by recent progress towards diamond heteroepitaxy on Si ͑001͒ using the bias technique. The proposal by Robertson that an initial graphitic deposit with the graphite planes normal to the Si surface ͑resulting from carbon subplantation͒ provides a well matched compliant buffer layer and hence may lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Thus the voltage bias is effective for reactions between carbon and hydrogen or between carbon and carbon. 11,12,31 A detailed calculation of the dynamical chemical reaction for various kinetic energies of hydrogen ions is required for the further discussion of nucleus formation of diamond in the microwave CVD process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the voltage bias is effective for reactions between carbon and hydrogen or between carbon and carbon. 11,12,31 A detailed calculation of the dynamical chemical reaction for various kinetic energies of hydrogen ions is required for the further discussion of nucleus formation of diamond in the microwave CVD process.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 A variety of the interface structures between the Si substrate and diamond layers formed during the bias pretreatment, such as SiC, 13,14 amorphous carbon, 15 and nanographite, 16 are directly observed by highresolution transmission electron microscopy ͑HRTEM͒. 17 The formed structures may essentially depend on the kinetic energy of the ions on the substrate surface which is dependent on the plasma parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The Gibbs free-energy DG 0 in the formation of SiC is calculated to be À63 kJ at 1643 K. Some researches, which relate to moleculardynamics of diamond/Si composites [15] and kinetics of the reaction of diamond/Si composites [16], have been reported. TEM study of the structure and chemistry of a diamond/silicon interface showed the evidence of b-SiC [17].…”
Section: In Situ Reactionmentioning
confidence: 99%
“…The ultimate goal of the diamond synthesis for the application in microelectronics would be the deposition of single-crystal diamond films in a large area on a low cost substrate such as silicon. In order to realize this aim, a lot of experimental and theoretical works [4][5][6][7][8][9][10][11][12] have been done. Especially, using the bias-enhanced nucleation (BEN) method, heteroepitaxial growth of diamond thin film has been made a great progress, [13][14][15][16] For example, oriented diamond films were synthesized on silicon substrates 12,13 and the interface structure between silicon and diamond [14][15][16] was observed directly with high resolution transmission electronic microscope (HRTEM).…”
mentioning
confidence: 99%